The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s11262-010-0523-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic reassortment between high-virulent and low-virulent Dobrava-Belgrade virus strains

Abstract: The tri-segmented RNA genome of hantaviruses facilitates genetic reassortment by segment swapping when cells are co-infected with different virus strains. We found efficient in vitro reassortment between members of two different genetic lineages of the Dobrava-Belgrade virus species, the weakly virulent DOBV-Aa and highly virulent DOBV-Af. In all reassortants, S and L segments originated from the same parental strain, and only the M segment was exchanged. To identify functional differences between the parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 54 publications
(76 reference statements)
1
19
0
Order By: Relevance
“…We observed the L segment reassortant and S segment recombinant of HTNV infected humans and caused HFRS, respectively28. Dobrava-Belgrade virus (DOBV) showed the reassortment of M segment between avirulent strain DOBV-Aa and virulent strain DOBV-Af in vitro 57. Thus, further studies are required to understand the biological and ecological consequences of recombination or reassortment in the MJNV population.…”
Section: Discussionmentioning
confidence: 94%
“…We observed the L segment reassortant and S segment recombinant of HTNV infected humans and caused HFRS, respectively28. Dobrava-Belgrade virus (DOBV) showed the reassortment of M segment between avirulent strain DOBV-Aa and virulent strain DOBV-Af in vitro 57. Thus, further studies are required to understand the biological and ecological consequences of recombination or reassortment in the MJNV population.…”
Section: Discussionmentioning
confidence: 94%
“…Host- and virus-specific determinants are discussed as reasons for the broad range of clinical pictures [15]. The most obvious differences exist between the clinical picture of hantaviral cardiopulmonary syndrome (HCPS) and HFRS caused by New and Old World hantaviruses, respectively [6].…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the use of entry receptors, in the regulation of cytokine response and in viral replication were described to be associated with pathogenicity [811]. Studies with genetic reassortants in vitro and in animal models suggest molecular determinants to be responsible for virulence [5, 12]. However, the species-specific factors of hantaviruses that are responsible for pathogenicity and clinical picture are not identified so far.…”
Section: Introductionmentioning
confidence: 99%
“…A readout marker for IFN bioactivity, which has been often used in characterization of hantaviruses, is the antiviral MxA protein [21][25]. The MxA protein belongs to the superfamily of dynamin-like GTPases and is involved in mediation of antiviral immune response against many viruses [26].…”
Section: Introductionmentioning
confidence: 99%
“…Hantaviruses are weak inducers of type I (α/β) interferon, however, a recent study revealed that hantaviruses are able to induce type III IFN (λ1–3) in type I IFN-deficient Vero E6 cells which are routinely used for generation of hantavirus stocks [30]. Therefore, influence of Vero E6-derived type III IFN on earlier observed DOBV MxA induction patterns [25] has to be investigated.…”
Section: Introductionmentioning
confidence: 99%